Assessment of Co-Creativity in the Process of Game Design - Romero, Margarida; Sylvester, Arnab; De Smet, Cindy; Fitri Suraya, Mohamad; Jacey Lynn, Minoi; Morini, Luca (Academic Conferences and Publishing International Limited, 2019)
We consider game design as a sociocultural and knowledge modelling activity, engaging participants in the design of a scenario and a game universe based on a real or imaginary socio-historical context, where characters can introduce life narratives and interaction that display either known social realities or entirely new ones. In this research, participants of the co-creation activity are Malaysian students who were working in groups to design game-based learning resources for rural school children. After the co-creativity activity, the students were invited to answer the co-creativity scale, an adapted version of the Assessment Scale of Creative Collaboration (ASCC), combining both the co-creativity factors and learners’ experiences on their interests, and difficulties they faced during the co-creativity process. The preliminary results showed a high diversity on the participants’ attitudes towards collaboration, especially related to their preferences towards individual or collaborative work.